(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2023)
This paper discusses how family history can be selected, read, and utilised in historical education to cultivate historical thinking among pupils aged between 16 and 18 years of age. The research derives its epistemological basis from the theories of memory and history, oral and family history, theory of historical consciousness, and historical thinking. Family history was used as a bridge that connects the past with the present. The research was carried out within the context of four family history action research projects. The narratives which were selected by pupils were analysed by the teacher/ researcher, based on how the pupils orientated their lives toward the past, present, and future. From the family stories of the pupils, individual acts of heroism and acts of life were highlighted within a wider indefinite historical context. The narration of these stories within the school environment raised a variety of questions about their historical context and second-order concepts, such as change through time, significance, causes, and consequences. The multiple phases of the activities as well as the exploratory tasks carried out, contributed to the realisation that living memory requires meaningful reading by the pupils, a critical approach, and the synthesising of their individual and collective pasts. Reflection during each phase of the research, more so at the end of the activities, highlighted teaching practices through which family memories can be used in the learning process, encouraging continuous and two-way interaction of individual and collective consciousness.